Methanolic Extract of Sikari Laharo (Periploca calophylla) has Analgesic Properties - Adhikari, J; Thapaliya, S; Shah, M.K.; Singh, S; Paudyal, N (Nepalese Veterinary Journal, 2023)
Avaibale within the full article